Sosialisasi Pentingnya Asuransi Bagi Umkm Oren's Laundry di Salakan Gamping Sleman - Sofiati; Vanisa Rahma Anindya; Novem Gardenia Ninik Primeri; Nurul Afifah; Aprilia Uswatun Khasanah; Ninda Putri Zulekha Sapta (JCSE: Journal of Community Service and Empowerment, 2025)
The laundry business has promising prospects due to increasing technological changes, but this service business carries many risks that are less recognized by MSMEs. The purpose of this community service activity is to raise awareness among MSMEs about the importance of insurance in protecting Orent's Laundry business risks. The activity was carried out on May 2 and 3, 2025, at the business location. The socialization method used in this activity involved students through counseling and discussions with demonstration examples to the participants, consisting of one owner and three employees. The results of the socialization showed high enthusiasm from the participants in managing a laundry business, proven by the participants' successful understanding of the risks and protection of laundry business insurance. The contribution of the results of this activity for interested partners is to consider registering for insurance for damage and loss of customer clothing at Orent's Laundry to satisfy customers and ensure the sustainability of the laundry business